Desirable TiO2 compact films for nanostructured hybrid solar cells. (2nd January 2020) - Yun, Jung-Ho; Lyu, Miaoqiang; Ahmed, Rasin; Triani, Gerry
ABSTRACT: Two different TiO2 compact films, fabricated by sol-gel spin-coating (SC) and spray-pyrolysis (SP) processes, were employed as an electron transport layer (ETL) to the nanostructured hybrid perovskite solar cells (PSCs), and they were comprehensively investigated through the various characterisation approaches using electrochemical and physicochemical approaches. With cyclic voltammetry and XPS results, the absence of pinholes on the SP-TiO2 compact films was indicated, and AFM and SEM results confirmed the SP-TiO2 compact films had lower surface roughness and more compact particle connectivity, offering a decent interface between the perovskite active layer and the adjacent TiO2 films. The performance of the SP-PSCs using the SP-TiO2 compact films was 7.06%, which was 3 times higher than that of the SC-PSCs. Voc decay measurement also confirmed that such pinhole-free and improved film interfaces of SP-TiO2 compact films contributed to elongating electron lifetime in PSCs by the enhanced hole blocking effect of the SP-TiO2 compact films.